A grounded theory model of service language in Australia's luxury hotels. (December 2017) - Scerri, Madalyn A.; Jenkins, John M.; Lovell, Genevieve
Abstract: This exploratory study critically analyzes service providers' spoken language in luxury (five-star) hotels. Informed by an interpretive research paradigm and a grounded theory methodology incorporating a concurrent process of data collection and analysis, semi-structured interviews were undertaken with 22 service providers employed in luxury hotels in the Central Business District of Sydney, Australia. Our findings reveal that service providers open and close their service encounters with hotel guests by using structured, and often rehearsed, sequences of verbal exchange. Between the opening and closing sequences, service providers' interactions and conversations with guests vary depending on the situations arising during encounters. Processes that allowed for flexibility and adaptation during encounters were important for transitions in service providers' verbal exchanges and building relationships with guests. A substantive grounded theory model for critically analyzing the language of service in Australian luxury (five-star) hotels is presented. Our research contributes to theoretical and applied understandings of service in five-star hotels broadly, and the language of service in particular. It adds to knowledge of the complexities and multifaceted characteristics of service provider – customer interactions, relevant to hospitality and broader service contexts.